Analysis of IT-Assisted PBL-Based Problem Solving Ability at Nurul 'Azizi Integrated Islamic Middle School - Siregar, Muhammad Fadhil Hidayat (Study Program of Mathematics Education of Unimed Postgraduate Program, 2024)
Quantitative and quasi-experimental methods were employed in the investigation. Help with IT issues from a technical standpoint Scholars hold freedom and education in high regard. We administered these tests to eighth graders at Nurul Azizi Integrated Islamic Middle School. Thirty pupils make up each of the two VIII B and VIII A Random classes. The study established two groups: one to serve as a control and another to serve as an experimental group. Compare and contrast VIIIA with VIIIB. The control group used more traditional methods, while the experimental group used problem-based learning based on information technology. a research project having a strong emphasis on numerical data and statistical analysis. A statistical analysis was conducted. To estimate or predict something about a broader population, sample statistics can be utilized. Using assumptions about the data's underlying distribution, parametric statistics involves drawing conclusions about population parameters. A hypothesis is tested before any experiments are conducted. 1) The term